Microinvasive Carpal Tunnel Release Using a Retractable Needle‐Mounted Blade. (20th September 2020) - Hebbard, Peter; Thomas, Peter; Fransch, Shaneil V.; Cichowitz, Adam; Franzi, Stephen
Abstract : We report 166 microinvasive ultrasound‐guided carpal tunnel releases using the MICROi‐Blade (Summit Medical Products, Inc, Sandy, UT), a needle‐based tool for cutting under ultrasound guidance. The 6‐month follow‐up of the first 21 cases, including 5 bilateral releases, showed a progressive reduction in median pain scores, Boston Carpal Tunnel Questionnaire (BCTQ) Symptom Severity Scale scores, and BCTQ Functional Status Scale scores. The median return to work was 7 days. The 3‐month follow‐up of 62 subsequent cases showed similar improvement in the BCTQ scores and return to work. There were no complications. This report supports the effectiveness of the technique.